2015
DOI: 10.1177/0954406215570702
|View full text |Cite
|
Sign up to set email alerts
|

Large amplitude vibrations of heated Timoshenko beams with delamination

Abstract: In this work, the large amplitude vibration of a heated Timoshenko composite beam having delamination is studied. The model of delamination considers the contact interaction between sublaminates including normal forces, shear forces, and additional damping due to the interaction of sublaminates. This work is an extension of the previous analysis based on a model of the dynamic behavior of a beam with delamination considering additionally the nonlinearities due to large displacements and temperature changes. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This method is more often used considering only the first mode, i.e., N modes ¼ 1. The method frequently gives additional, false peaks and it is not widely used for real applications (Manoach et al 2016a).…”
Section: Modal Slopementioning
confidence: 99%
“…This method is more often used considering only the first mode, i.e., N modes ¼ 1. The method frequently gives additional, false peaks and it is not widely used for real applications (Manoach et al 2016a).…”
Section: Modal Slopementioning
confidence: 99%
“…Hu et al (1999) suggested artificial springs to model the contact forces between delaminated segments based on Midlin plate theory in the buckling behavior of laminate structures. Manoach et al (2016) investigated the effect of large deflections and evaluated temperature on the vibration of delaminated Timoshenko composite beam. In this study, damping due to the interaction of sub-laminates was discussed in detail.…”
Section: Introductionmentioning
confidence: 99%